Breast cancer: knowledge, attitude and practices among undergraduate female students at a government college in Koppal, Karnataka - Nimbannavar, Smita M.; Mane, Vijaykumar P. (International Journal Of Community Medicine And Public Health, 2019)
Background: Breast cancer is the second most common malignancy in general and most common cancer among women in both the developed and developing countries. Its incidence is on the raise due to increased life expectancy of people, increased urbanization and adoption of unhealthy lifestyles. An awareness of brest cancer and its presentation is essential among women for detection at an early stage and timely treatment for better prognosis. The objective of the study was to assess knowledge, attitudes and practices towards breast cancer among female students in the study setting. Methods: A descriptive study was conducted for duration of 3 months from July 2018 to September 2018 among female students at a degree college in Koppal city, Karnataka. A total of 396 students were included and data was collected using a pre tested and semi structured questionnaire after taking an informed consent. Data thus obtained was entered and analyzed using Microsoft Office Excel 2013. Results: More than 80% of study participants had heard about breast cancer in the present study but their knowledge on its various aspects was limited. More than half were positive in their attitude believing that they are not at risk of breast cancer and were willing to practice breast self-examination (BSE) in future but only 5.28% of them admitted to have done BSE in the past. Most common source of information about disease was school in the present study. Conclusions: The present study demonstrated KAP gap among graduate female students which needs to be tackled through proper educational interventions.